Analysis of Culinary Innovations Food Street Vendors From Society in Timor-Leste: Case Study of Street Vendors in Dili Municipality - Soares, Joao Antonio; Menezes, Frans Belarmino Dos Santos (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
Culinary business or food business is a household-scale business that has good opportunities for now and in the future. In the business market in the national capital (Dili), the need for streets vendors canteen roadside, continues to flow. But the reality is, if less creativity from society to take part in culinary business to express their creative abilities and innovation to the public through culinary entrepreneurship activities. Although many societies take part in the training, but many of them also lack the conscience to use the science that they get to implement in their lives. The research methodology used by the research team in this research is SOWT Analysis and qualitative descriptive, for primary data to analyze and interpret According to experts Milles and Huberman in the book Sugiono 2018, with data collection techniques and data analysis techniques. The results of the research showed that culinary food street vendors have shown positive signs because they can create jobs for themselves, and also make many innovations from their creative skills such as culinary combinations of food from Europe and ASEAN (Indonesia) etc. The conclusion of this research shows that; When Timorese culinary food streets vendors to compete with foreigners is the main step is the potential strategy for growth is to consider finding investors, make a marketing plan, big first plan and plan to use accounting software, so that Timorese culinary mobile vendors children can compete and promote original Timorese culinary food to domestic and foreign consumers.